The Effectiveness of the Implementation of Customary Fines in Settlement of Seclusion Cases in Banda Aceh - Teuku Muttaqin Mansur; Yunita Yunita; M Adli; Sulaiman Sulaiman (Faculty of Law, Sriwijaya University, Indonesia, 2020)
Seclusion (khalwat) is the activity conducted in a quiet place between two individuals of different sex who are not mahram (blood relative) without the legitimate marriage bond and the willingness from both parties, which leads to adultery. Fine is one of the customary penalties given to the perpetrators of khalwat. In practice, implemented of fines between one region and another is different. The study aims to identify the types of adat fines charged to khalwat perpetrators and the effectiveness of implementation on the settlement customary fines in Banda Aceh. It used a juridical-empirical research method. The data used, in addition to primary and secondary legal material, also used an in-depth interview with respondents. The data analyzed using a qualitative descriptive approach. This research conducted in Banda Aceh district. The research results show that the kind of customary fines given to khalwat perpetrators was different. There are even some cases begun to shift, and some considered that being married because of khalwat was considered one of the customary fines. Customary fines are effective in reducing offense of khalwat. However, there are concerns if the decision of the customary fines does not get optimal support from law enforcement officials. Expected, customary official affirmed kind of customary fine given to khalwat perpetrators. The difference subtle, need to consider the aspect of justice, the ability, and effective whereabouts of fines to reduction offense of khalwat.